Comment les équipes éducatives prennent-elles en compte la situation d’enfants atteints du diabète de type 1 ? Analyse du propos des enseignants en Belgique francophone - Pauline Delannoy; Hélène Geurts; Antoine Derobertmasure (Éducation et Socialisation)
This study aims to collect the experiences of twenty primary teachers in French-speaking Belgium related to the caring of children with type 1 diabetes as well as the strategies deployed in order to promote the school inclusion of this public with specific medical needs. The analysis of the semi-structured interviews reveals that the reception of these pupils represents a great responsibility which can generate emotional difficulties. In addition, two other major observations were made: first, the almost total absence of knowledge of the administrative and legal framework inherent in the support of diabetic children at school and, second, a potential incompatibility between the reasonable arrangements made by teachers and the cases anticipated by the legislator. These results underline the importance to promote initial and ongoing training on the frameworks and issues of school inclusion, as well as the legal changes needed to ensure that teachers' practices are in line with legal requirements.